Chiral Recognition of Tyrosine Enantiomers Based on Decreased Resonance Scattering Signals With Silver Nanoparticles as Optical Sensor. Issue 3 (12th December 2014) - Tan, Xuanping; Li, Qin; Shen, Yizhong; Wu, Huan; Zhao, Yanmei; Yang, Jidong
Abstract A novel chiral sensing platform, employing silver nanoparticles capped with N‐acetyl‐L‐cysteine (NALC‐Ag NPs), was utilized for the discrimination of L‐tyrosine and D‐tyrosine. This nanosensor, which could be used as an optical sensing unit and chiral probe, was characterized by transmission electron microscopy (TEM) and resonance Rayleigh scattering (RRS) spectroscopy. After the proposed sensing platform interacted with L‐tyrosine and D‐tyrosine, a decreased resonance scattering signal was only obtained from L‐tyrosine. This phenomenon offered a useful assay for the selectivity and determination of L‐tyrosine with the RRS method. The linear range and detection limit of L‐tyrosine were 0.2838–20.0 µg⋅mL‐1 and 0.0860 µg⋅mL‐1, respectively. In addition, experimental factors such as acidity, interaction time, and the concentration of enantiomers were investigated with regard to the effect on enantioselective interaction. Chirality 27:194–198, 2015. © 2014 Wiley Periodicals, Inc.